1977
DOI: 10.1073/pnas.74.11.4955
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin regulation of macrophage collagenase production.

Abstract: The production of collagenase (EC 3.4.24.3) by endotoxin-stimulated macrophages was significantly inhibited by indomethacin, indicating that prostaglandins (PGs) mediate this effect. Inhibition of collagenase production by indomethacin was overcome by addition of exogenous PGE2 at 10 nM whereas the addition of 0.1 and 1.0MgM PGE2 increased the enzyme production to 3 times that achieved by endotoxin. Although the addition of prostaglandin alone to macrophage cultures did not stimulate collagenase production, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(67 citation statements)
references
References 19 publications
2
65
0
Order By: Relevance
“…Therefore, regulation of signal transduction events that are associated with the production of inflammatory mediators, such as MMPs, has been of considerable interest. A PGE 2 -cAMP-dependent pathway leading to the production of MMP-1, MMP-9, and MMP-7 (matrilysin) by activated monocytes has been demonstrated previously (13,16,(23)(24)(25)(26). In the present study, we have demonstrated that LPS induces monocyte MT1-MMP and that the signaling pathway for MT1-MMP synthesis involves, in large part, a PGE 2 -dependent mechanism.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, regulation of signal transduction events that are associated with the production of inflammatory mediators, such as MMPs, has been of considerable interest. A PGE 2 -cAMP-dependent pathway leading to the production of MMP-1, MMP-9, and MMP-7 (matrilysin) by activated monocytes has been demonstrated previously (13,16,(23)(24)(25)(26). In the present study, we have demonstrated that LPS induces monocyte MT1-MMP and that the signaling pathway for MT1-MMP synthesis involves, in large part, a PGE 2 -dependent mechanism.…”
Section: Discussionmentioning
confidence: 62%
“…Effect of PGE 2 on Monocyte MT1-MMP Expression-The induction of MMPs in monocytes by agents such as concanavalin A, LPS, or secreted protein, acidic and rich in cysteine, has been shown to occur through a prostaglandin-dependent pathway (13,16,(23)(24)(25)(26). To determine whether monocyte MT1-MMP production is regulated through this pathway, monocytes were pretreated with indomethacin for 1 h and then stimulated with LPS in the absence or presence of PGE 2 .…”
Section: Effect Of Lps On Monocyte Mt1-mmp Rna and Protein-mentioning
confidence: 99%
“…However, these synovial cells prodtuce prostaglandins, particularly PGE2, in relatively high anuiotiunts. Although PGE2 can modulate collagenase production by rodent macrophages (23), as well as bv huiman rheumatoid synovial cells (24), the amount of PGE2 in the mononuclear cell media used in the present studies cannot account for the observed effects on collagenase production by synovial cells, and monocytes incubated in the presence of indomethacin still release collagenase-stimulating factor (25).…”
Section: Discussionmentioning
confidence: 92%
“…Other work from our laboratory has demonstrated that monocytes directly resorb both devitalized bones by a mechanism which is not mediated by the action of osteoclasts (25) and live bones through an osteoclast-mediated mechanism which is prostaglandin-dependent (26). There is also other evidence which suggests that monocytes and macrophages synthesize and release PGs (27)(28)(29), collagenase (30), and hydrolytic enzymes (31), which are all capable of resorbing bone or degrading bone matrix. It is also possible that circulating mononuclear cells may transform or differentiate into osteoclasts (32).…”
Section: Discussionmentioning
confidence: 93%